(3CWdS GdaJhMGJ GdESdGejI aj YgO GdNdaGA GdQGTOjf QVj Gddg Yfge (B/s - (3GdeZdhK, SGej YHO Gddg,s 1382 (3gLQj(B-s ((3GdQjGV (B:s (3ecJHI GdYHjcGf,s, 2015)
(3jJfGhd cJGH CWdS GdaJhMGJ GdESdGejI aj YgO GdNdaGA GdQGTOjf QVj Gddg Yfge GdehVhY ef NdGd bSeGf GdbSe GdChd aj GdaJM GdESdGej Ydi GdLHgI GdTQbjI (B((3GdYQGb hEjQGf hGdCbGdje GdESdGejI GdeLGhQI dgG (B) (3hajg HGHGf GdHGH GdChd aj aJM GdYQGb, GdHGH GdKGfj aj aJM EjQGf hGdCbGdje GdeLGhQI dgG(B. (3GdbSe GdKGfj aj GdaJM GdESdGej Ydi GdLHgI GdZQHjI (B( (3HdGO GdTGe heUQ hGdCbGdje GdeLGhQI dgG (B) (3hajg KdGKI CHhGH, GdHGH GdChd aj aJM HdGO GdTGe hGdCbGdje GdeLGhQI dgG, GdHGH GdKGfj aj aJM CQejfjG hGdHdGO GdeLGhQI dgG, GdHGH GdKGdK aj aJM eUQ hCLRGA ef GdShOGf GdTeGdj hdjHjG hEaQjbjI (B((3JhfS(B)(3, hHg eLehYI eUWdMGJ aj GdeSGaGJ hGdeSGMGJ hGdfbhO(B.s
Keywords: (3GdaJhMGJ GdESdGejIs -- (3YUQ UOQ GdESdGes -- (3CWGdSs; (3GdJGQjN GdESdGejs -- (3YUQ UOQ GdESdGes -- (3CWGdSs